Implementasi Supervisi Pembelajaran di Sekolah Dasar: Studi Kasus Komparatif Empat Sekolah di Kota dan Kabupaten Malang - Afnani Thoyibah; Maisyaroh Maisyaroh; Ahmad Nurabadi (CV. Global Cendekia Inti, 2026)
This study aims to explore, compare, and analyze the implementation of learning supervision in four elementary schools in Malang City/Regency representing different school typologies: public school, public madrasah, university laboratory school, and private Islamic school. A qualitative approach with a multiple case study design was employed. Data were collected through in-depth interviews with principals, teachers, and school supervisors (12 informants), four-session field observations, and document analysis. Findings reveal that all four schools have implemented supervision with different models and approaches: (1) SDN Mulyoagung 1 applied non-directive TIRTA-coaching within the HARAPAN program; (2) MIN 2 Kota Malang developed an eight-group collegial supervision system supported by the SIMIDUN application; (3) SD Laboratorium UM employed a 7-Form Format with a collaborative per-grade approach within a dual curriculum framework (Cambridge and Merdeka Curriculum); and (4) SD Muhammadiyah 8 Dau integrated classroom video reflection and a learning community in the MAPAN program. Supervision outcomes demonstrated average PAS score improvements ranging from 1.6 to 9.3 points. Learning mastery increased from 72% to 81% in SD-A. The dimensions most differentiating across schools were feedback quality and consistency of follow-up plan monitoring. This study produces a comparative analytical framework for elementary school learning supervision considering school typology context, and recommends evidence-based coaching approaches and the integration of professional learning communities as strategies for sustainable quality improvement.